Correlation of Speckle-Tracking Echocardiography with Traditional Biomarkers in Predicting Cardiotoxicity among Pediatric Hemato-Oncology Patients: A Comprehensive Evaluation of Anthracycline Dosages and Treatment Protocols - Andrada Mara Ardelean; Ioana Cristina Olariu; Raluca Isac; Ruxandra Jurac; Cristiana Stolojanu; Mircea Murariu; Ana-Olivia Toma; Laurentiu Braescu; Adelina Mavrea; Gabriela Doros (MDPI AG, 2023)
Speckle tracking-echocardiography (STE) is a novel non-invasive imaging tool capable of quantifying myocardial deformation, and thus holds promise in detecting early subclinical myocardial injury. This study aimed to evaluate the correlation of STE with traditional biomarkers in predicting anthracycline-induced cardiotoxicity in the context of varying dosages and treatment protocols in pediatric hemato-oncology patients. We conducted a retrospective study involving pediatric hemato-oncology patients undergoing anthracycline-based chemotherapy. A total of 99 patients were included in the final analysis, with 82 receiving Doxorubicin, of which 58.5% were males, and 17 receiving Epirubicin, of which 70.6% were males, with a median of 10 years old. Traditional biomarkers, such as Troponin I (cTnI) and B-type natriuretic peptide (BNP), were compared with STE parameters, including the global longitudinal strain (GLS), Simpson method of discs (SMOD), and myocardial performance index (MPI). A comprehensive evaluation was conducted based on different dosages of anthracyclines and different treatment protocols, with a follow-up period of one year post-chemotherapy. It was observed that the cTnI levels in the Doxorubicin group were significantly higher (3.2 ng/mL, p = 0.002) than in the Epirubicin group (2.7 ng/mL). However, BNP and NT-proBNP levels were not significantly different between the two groups (p = 0.096 and p = 0.172, respectively). Regarding STE parameters, a significant negative correlation was observed between the anthracycline dose and GLS (Rho = −0.411, p = 0.001), indicating increased cardiotoxicity with dose elevation. The SMOD and MPI gave significantly better values in the Epirubicin group (59.2 and 0.41 vs. 54.4 and 0.36, respectively). However, the ROC analysis did not find GLS, SMOD, or MPI to be significant independent predictors of cardiotoxicity (p > 0.05). There was also considerable variation in cardiotoxicity between the Doxorubicin and Epirubicin study groups, suggesting that the risk of cardiotoxicity is not solely determined by dose. Our study underlines the potential of STE as a sensitive tool for the early detection and prediction of anthracycline-induced cardiotoxicity in pediatric hemato-oncology patients, but only in association with the clinical findings and cardiac biomarkers. While traditional biomarkers still play a role, STE can offer a more accurate prediction of cardiac risk, potentially leading to better management and outcomes for these patients.